Optimization of selective assembly and adaptive manufacturing by means of cyber-physical system based matching. Issue 1 (2015) - Lanza, Gisela; Haefner, Benjamin; Kraemer, Alexandra
Abstract In high-tech production, companies often deal with the manufacturing of assemblies with quality requirements close to the technological limits. Selective and adaptive production systems are means to cope with this challenge. In this context new measurement technologies and IT-systems offer the opportunity to generate and use real-time quality data along the process chain and to control the production system adaptively. In this article, a holistic matching approach to optimize the performance of selective and adaptive assembly systems is presented and its industrial application within an automotive electric drive assembly is demonstrated.